Implementation of Narrative Essay Learning Strategies for Elementary School Writing Level - Astutik, Dwi Widi; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra; Anggraini, Ade Eka; Mardhatillah (Journal of Education Action Reseach, 2024)
Writing narrative essays is one of the language skills that elementary school students must have. The use of interesting methods and media is used to stimulate students to develop narrative essay storylines. Several variations of learning strategies are offered so that students can develop their writing skills. This research aims to analyze learning strategies for writing narrative essays that are suitable for use in elementary schools. This research uses a qualitative method with a case study approach. The population of this research was carried out on class IV students as a data source. Data collection techniques include document analysis, questionnaires, observations and interviews. Based on the research results, the strategies used in learning to write narrative essays are not appropriate. Students have not been able to develop sentences in narrative essays based on the series of pictures presented. Lack of practice and lack of interest in reading are the dominant reasons why students are weak in writing.  The implications of this research are can provide new insights for teachers in designing and implementing writing lessons that are more effective and interesting for students. With narrative essay strategies, students can more easily develop their critical thinking skills and creativity through telling personal or imaginative experiences.